Corporate Image Management through Social Media: Literature Review of Research before and during the Covid-19 Pandemic - Tatak Setiadi (Metafora: Education, Social Sciences and Humanities Journal, 2023)
The continuity of a company's business processes that have a good image will have an impact on a good company reputation. This article attempts to provide a literature review on the role of information and communication technology in building corporate image through social media before and during the Covid-19 pandemic. During the pandemic, reputation is an asset that can help a company to get through any difficult times. In addition, reputation will add to the market value of a company. As an element of reputation, corporate image needs to be built so that it can be beneficial for the company and can increase market value, especially amidst the Covid-19 pandemic. The discussion about corporate image developed since Abratt (1989) and Nguyen & LeBlanc (1998) offered a new approach in corporate image management. The study conclude that in certain ways companies need various strategies in building their image including by using social media power to deliver positive information to publics.